Population trends of Northern Lapwing, Eurasian Curlew and Eurasian Oystercatcher over 15 years in a southwest Norwegian farmland - Byrkjedal, Ingvar; Kyllingstad, Kåre; Efteland, Svein; Grøsfjell, Steinar (Ornis Norvegica, 2012)
Northern Lapwing Vanellus vanellus, Eurasian Curlew Numenius arquata, and Eurasian Oystercatcher Haematopus ostralegus were censused annually around 20 April, between 1997-2011, along a standardized route in Jæren, SW Norway. The area censused comprises 2972 ha, consisting of grassland, arable land, improved pasture, and heather moor. The area is intensively farmed, but has since long been a core area for breeding Lapwing and Curlew, and inland breeding of Oystercatchers has a history of several decades. Number of censused Lapwings along the route varied between years from 137 to 497, Curlews from 18 to 55 and Oystercatchers from 15 to 81. Linear regressions showed a statistically significant decline in Lapwings over the whole census period, while significant negative linear trends were found in numbers of Curlews and Oystercatchers over the 10 and 8-9 last years, respectively. The negative trend of the latter two species seems to have stopped in more recent years. Estimated from the regressions Lapwing numbers have declined by 44% over the census period, and by 53% when estimated from counts of the number of males. Since the trend is found in a core area of the species, this is a worrying situation for the Lapwing as a breeding bird in this region of Norway. The decline of Lapwing and Oystercatcher was more pronounced in cropland than in pasture habitats, indicating an effect from agricultural activities.